Caricature of Arthur Becket Lamb (1880-1952) - Weller, J.C. (1931)
Caricature of American chemist Arthur Becket Lamb (1880-1952) created by artist J.C. Weller at the 1931 American Chemical Society National Meeting in Buffalo, New York. Lamb served as the head of research for the Chemical Warfare Service during World War I and subsequently served as President of the American Chemical Society (1933), as well as editor of the Journal of the American Chemical Society.
Keywords: Lamb, Arthur Becket, 1880-1952; Chemists; Portraits; American Chemical Society; Caricatures and cartoons